Vitrectomy with or without internal limiting membrane peeling for idiopathic epiretinal membrane: A meta-analysis. - Wei-Cheng Chang; Chin Lin; Cho-Hao Lee; Tzu-Ling Sung; Tao-Hsin Tung; Jorn-Hon Liu (PLoS ONE)
Background Studies on vitrectomy with and without internal limiting membrane (ILM) peeling for idiopathic epiretinal membrane (ERM) have yielded uncertain results regarding clinical outcomes and recurrence rates. Objective To compare the clinical outcomes of vitrectomy with and without ILM peeling for idiopathic ERM. Methods Databases, including PubMed, Embase, Cochrane, Web of Science, Google Scholar, CNKI databases, FDA.gov, and ClinicalTrials.gov, published until July 2016, were searched to identify studies comparing the clinical outcomes following vitrectomy with ERM and ILM peeling and with only ERM peeling, for treating idiopathic ERM. Studies with sufficient data were selected. Pooled results were expressed as mean differences (MDs) and risk ratios (RRs) with corresponding 95% confidence intervals (CI) for vitrectomy with and without ILM peeling with regard to postoperative best corrected visual acuity (BCVA), central retinal thickness (CRT), and ERM recurrence rate. Results Eleven retrospective studies and one randomized controlled trial involving 756 eyes were identified. This demonstrated that the postoperative BCVA within 12 months was significantly better in the non-ILM peeling group (MD = 0.04, 95% CI: 0.00 to 0.08; P = 0.0460), but that the patients in the ILM peeling group had significantly better postoperative BCVA after 18 months (MD = -0.13, 95% CI: -0.23 to -0.04; P = 0.0049) than did those in the non-ILM peeling group. The non-ILM peeling group exhibited a higher reduction in postoperative CRT (MD = 51.55, 95% CI:-84.23 to -18.88; P = 0.0020) and a higher recurrence rate of ERM (RR = 0.34, 95% CI:0.16 to 0.72; P = 0.0048) than did the ILM peeling group. However, the improvement rates of BCVA (RR = 1.03, 95% CI:0.72 to 1.47; P = 0.8802) and postoperative CRTs (MD = 18.15, 95% CI:-2.29 to 38.60; P = 0.0818) were similar between the two groups. Conclusions Vitrectomy with ILM peeling results in better visual improvement in long-term follow-ups and lower ERM recurrence rates, and vitrectomy with only ERM peeling is more efficacious in reduction of CRT than is vitrectomy with ILM peeling.